2004
DOI: 10.3136/fstr.10.261
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Oleic and Linoleic Acids in Subcritical Water

Abstract: The solubility of oleic and linoleic acids in water was measured in the range from 60'C to 230'C at 15 MPa. The solubility of oleic acid was almost the same as that of linoleic acid in this range, and the solubility of the fatty acids was higher at higher temperature. The logarithm of the solubility of the fatty acids was related to the reciprocal of the absolute temperature by a linear equation with a negative slope at temperatures above 150'C, and the enthalpy of the solution of each fatty acid in the liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…The k u values obtained here can be compared to values reported in the literature for relatively simple substrates, such as methyl formate and ethyl formate (36) , ethyl acetate (12) , several aliphatic methyl and butyl esters with carboxylate group ranging from 8 to 16 carbons (37) , prepolymers for UP resins (38) , PLA (39) and other aliphatic polyesters (40) , and a polyester urethane (41) . The k u values were deduced by using simple assumptions (first order kinetics for ester consumption at low conversion rate) and are plotted in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The k u values obtained here can be compared to values reported in the literature for relatively simple substrates, such as methyl formate and ethyl formate (36) , ethyl acetate (12) , several aliphatic methyl and butyl esters with carboxylate group ranging from 8 to 16 carbons (37) , prepolymers for UP resins (38) , PLA (39) and other aliphatic polyesters (40) , and a polyester urethane (41) . The k u values were deduced by using simple assumptions (first order kinetics for ester consumption at low conversion rate) and are plotted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Some k u and k c values have been reported in the literature for auto-catalyzed hydrolyses (12,(36)(37)(38)(39)(40)(41)(42) . For instance, Krammer and Vogel (12) presented a plot for the hydrolysis of ethyl acetate, which displays a curvature from which A can be assessed by using (11) and the time for consuming half the initial esters.…”
Section: Figurementioning
confidence: 99%
“…C 5 H 11 COO À + H 3 O + ) almost all HA molecules carry a single negative net charge at the given pH value. Secondly, we choose stearic acid (SA, C 18 H 36 O 2 ), a long-chain fatty acid with a very low solubility in water (smaller than 1 mM [30]). As a result of the formation of premicellar aggregates, the pK a value of SA strongly depends on its concentration.…”
Section: à2mentioning
confidence: 99%
“…We measured their solubility in the temperature range from 60 to 230 1C, and showed that their solubility at 200 1C or higher temperatures was hundreds-fold or a thousand-fold higher than that at ambient temperature (Khuwijitjaru, Adachi, & Matsuno, 2002;Khuwijitjaru, Kimura, Adachi, & Matsuno, 2004a). Based on these measurements, we devised a novel method to prepare a finely dispersed oil-inwater (O/W) emulsion by mixing water containing a dissolved fatty acid at a high temperature and a surfactant solution, and confirmed the realization of the method (Khuwijitjaru, Kimura, Matsuno, & Adachi, 2004b).…”
Section: Introductionmentioning
confidence: 99%